JUDICIOUS USE OF L1: A SOCIOCULTURAL INVESTIGATION OF TEACHERSâ€™ USE OF L1 IN L2 CLASSROOMS - Khonamri, Fatemeh (International Journal of Education, 2017)
This study is a sociocultural investigation of the reasons why teachers use L1 in L2 classes through different classroom â€œmodesâ€ (Walsh, 2011). So far, a few studies regarding L1 have focused on L1 use in different classroom contexts, and none have used Walshâ€™s model of classroom modes. To this end, the present study used Walshâ€™s model which quarters the classroom context along with the Conversation Analysis techniques, to meticulously examine the classroom interactions. The classes were chosen from three different teachers in Mazandaran, Iran. A total of 6 sessions were recorded and transcribed. Results suggest that teachers use L1 mostly for managing purposes: drawing studentsâ€™ attention, and making sure they have comprehended what they are supposed to do, and educational purposes: explaining difficult grammar and vocabulary, and eliciting desired structures or utterances. These findings might help teachers use L1 more efficiently and judiciously, instead of avoiding it when and where it might benefit the learners, as well as minimizing it in their classes as much as possible.